Nontargeted metabolomics predicts the storage duration of white teas with 8-C N-ethyl-2-pyrrolidinone-substituted flavan-3-ols as marker compounds. (November 2019) - Xie, Dongchao; Dai, Weidong; Lu, Meiling; Tan, Junfeng; Zhang, Yue; Chen, Mei; Lin, Zhi
Abstract: Storage has a dramatic influence on the chemical composition, sensory qualities, biological activity, and therefore the commercial value of white tea. In this study, the metabolites in white teas stored for 1, 3, 7, and ≥ 10 years were comprehensively compared by a nontargeted metabolomics investigation. Most metabolites, including catechins, flavonol/flavone glycosides, amino acids, nucleosides, organic acids, aroma precursors, lipids, and carbohydrates, decreased with increasing storage duration, while 8-C N-ethyl-2-pyrrolidinone-substituted flavan-3-ols (EPSFs) and pyroglutamic acid increased. The absolute quantifications of 24 storage-related compounds combined with linear regression analysis showed that a panel of 5 indexes based on EPSFs has a good predictive ability for the storage duration of white teas (correlation coefficients were 0.9294 and 0.8812 in the model and test sets, respectively). The errors between the predicted and the actual storage durations ranged from −1.75 to 1.84 years for the white teas stored for <10 years. Graphical abstract: Unlabelled Image Highlights: Metabolomics and absolute quantification were applied to study stored white teas. Contents of 104 metabolites in stored white teas were compared. 27 metabolites were identified as being primarily storage-related. EPSFs contents showed good predictive ability for the storage durations.